An ontological exploration of change and constancy - Loubser, Ananka (Koers, 2013)
The history of philosophy presents a variety of viewpoints regarding the ontological primacy of either change or constancy. Some views regard change as foundational, to the point where constancy is denied (e.g. Heraclitus). Other views regard constancy as so important, that change becomes unthinkable (e.g. Parmenides). The apparent dialectical tension between the different conceptions demands an ontological clarification of these issues. This study illustrates and evaluates the relationship between change and constancy in the viewpoints of various philosophers and scientists throughout history. This is done by appropriating a reformational insight that change and constancy exist in cohesion. The study finds that the relationship between change and constancy is not dialectical, but rather one of integration, seated in irreducible primitive domains (modalities). The purpose of the article is twofold (1) to show that change and constancy cannot be reduced to one another but can only exist in a relationship of coherence and (2) to contribute a systematic clarification of framework change in terms of the relationship between change and onstancy on the ontological level.